Factors Associated with Non-Enrollment in National Health Insurance Scheme in Kaski District, Nepal - Adhikari, Anju; Gahatraj, Nand Ram; Yadav, Dipendra Kumar (Nepalese Journal of Insurance and Social Security, 2020)
Health insurance poses a vital role in developing countries, to attain an equitable health outcome to all citizens by ensuring universal health coverage. This study aims to assess the factors associated with non-enrollment in National Health Insurance Scheme (NHIS) in a setting of Nepal. A cross-sectional study was conducted among 492 households (246 non-enrolled and 246 enrolled) of Kaski district, Nepal from May to August 2020. Data were gathered from face-to-face interview. Data were entered in Epi data 3.1 and analysed by using statistical package for social sciences (SPSS16). Descriptive and inferential statistics were performed to analyze the data. The household without elderly family members were 2.06 times less likely to enroll in the scheme (AOR=2.060, CI=1.141-3.721, p<0.01). Similarly, non-enrollment increases with the decreasing wealth quintile of the family (AOR=4.312, CI=1.881-9.880, p<0.001). Families who perceived their family health status as fair was more likely to join the scheme than those as a good health status. Households who had poor or average knowledge on the scheme were almost five times more likely to non-enrollment (AOR=4.641, CI=2.841-7.582, p <0.001). Factors that determine the non-enrolment in NHIS are households had without elderly family members, poor wealth quintile, self-perceived good health status and poor knowledge on NHIS. Effective coordination from different stakeholders need to increase the health insurance coverage and increase the health literacy through the wide coverage of health communication program.